INVESTIGATION OF PARAMETERS AFFECTING THE OPTIMUM THERMAL INSULATION THICKNESS FOR BUILDINGS IN HOT AND COLD CLIMATES - Canbolat, Ahmet Serhan; Bademlioğlu, Ali Hüsnü; Saka, Kenan; Kaynakli, Omer (Vinca Inst Nuclear Sci, 2020)
This paper investigates the factors affecting the optimum insulation thickness and its pay-back period, such as heating and cooling energy requirements of building, lifetime, present worth factor, costs of insulation material and installation, costs of energy sources for heating and cooling, heating and cooling system efficiencies, and solar radiation. For this purpose, by considering two cities characterizing the hot and cold climatic conditions, the optimum insulation thickness and its payback period have been calculated and a detailed parametric analysis has been carried out. To achieve practical results, the ranges of the parameters considered in the study include the values typically reported in the literature. The variations in the optimum insulation thickness and the pay-back period with all parameters are presented in graphical form. Finally, order of importance and contribution ratios of the examined parameters on the optimum insulation thickness are determined with the help of Taguchi method. It is found that heating degree-days is the most efficient parameter on the optimum insulation thickness with an impact ratio of 27.33% of the total effect while the least efficient parameter is the efficiency of heating system with an impact ratio of 3.21%.
Keywords: optimization; thermal insulation thickness; energy conservation; life-cycle cost; Taguchi